Development and evaluation of enzyme-linked immunosorbent assays for the detection of gelatin sources - Tukiran, Nur Azira (2016)
Gelatin is derived from partial hydrolysis of type I collagen (connective tissues such as skin, bone, tendon and ligament), which is commonly obtained from mammalian sources (bovine and porcine). However, the use of gelatin derived from mammalian sources in confectionery and pharmaceutical products have become a controversial issue regarding to religious and health concern. Additionally, it was reported that porcine gelatin has been surreptitiously added to edible bird’s nests (EBNs) to increase their net weight prior to sale. Thus, a reliable technique for the determination and detection of gelatin sources is necessary in order to protect and reassure consumers against food fraud. This study concerns two issues; (i) determination of gelatin sources in confectionery and pharmaceutical products and (ii) determination and detection of porcine gelatin adulterant in EBN. There are some reports for gelatin sources differentiation by analysis of their amino acids. Those specific peptides can be used as specific biomarkers for gelatin sources differentiation and detection. Thus the aims of this study were to develop and evaluate the potential biomarker of porcine marker peptides using enzyme-linked immunosorbent assay (ELISA) for the detection and determination of porcine gelatin in processed products. Collagen α2 (I) chain protein of 125 kDa molecular weight showed resistance against heat and detectable in the studied commercial processed products when analyzed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). Three porcine species-specific amino acid sequences of GFPGSPGNVGPAGK (Peptide 1) and GIPGEFGLPGPAGPR (Peptide 2) of collagen α2 (I) chain and SGDRGETGPAGPAGPVGPVGAR (Peptide 3) of collagen α1 (I) chain were selected for raising polyclonal antibodies (pAbs). Three competitive indirect ELISAs were developed using pAbs against the aforementioned porcine species-specific amino acid sequences of collagen α2 (I) chain to obtain pAb1 and pAb2, and α1 (I) chain to obtain pAb3. The limit of detection (IC15) of the three competitive indirect ELISAs was 0.033, 0.082 and 0.052, μg/mL respectively. The median inhibitory concentration (IC50) of pAb1, pAb2 and pAb3 was 0.265, 0.394 and 0.228 μg/mL, respectively. All pAbs were able to recognize mammalian gelatin, while pAb2 and pAb3 exhibited moderate cross-reactivity (≤15 – 1%) toward fish and chicken gelatin. The specificity of the developed ELISAs was not influenced by the process type (type A or type B) and the origin of the collagen (skin or bone). Fourier transform infrared spectroscopy (FTIR) results showed that slight difference of the infrared spectra between Amide II and III regions of gelatin may influence the sensitivity of this immunoassay. Seventy commercially processed products (i.e. jellies, gummies, premix powders and hard shell capsules) were examined, 7% of samples showed false-positive results when analyzed using competitive indirect ELISA based on pAb2. Competitive and non-competitive ELISAs were developed as to provide quantitative and qualitative measurements of porcine gelatin in EBN respectively. Based on developed competitive ELISAs, pAb1 and pAb2 have showed moderate crossreactivity with cave nest and blood cave nest, respectively. Both pAbs exhibited moderate cross-reactivity with egg white. No cross-reactivity (<1%) was observed with EBNs and egg white for pAb3. pAb3 has showed best sensitivity, specificity, accuracy and repeatability compared to pAb2 and pAb1. While for non-competitive indirect ELISAs, all pAbs were able to detect at least 0.05% porcine gelatin in spiked samples of EBNs. However, pAb1 exhibited slight cross-reactivity toward orange, cave and house nests. In conclusion, the study indicated that the developed ELISAs utilizing the anti-peptide pAbs would be a good strategy for the detection and determination of gelatin sources in processed products.